RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP OF HEAD NURSES AND ORGANIZATIONAL COMMITMENT OF REGISTERED NURSES IN CRITICAL CARE UNIT, POLICE GENERAL HOSPITAL - Rujiwatchara-olun, Benchawan (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
The purposes of this research were to examine the relationship between the transformational leadership of head nurses and the organizational commitment of registered nurses in the critical care unit, Police General Hospital. The samples were recruited 90 nurses who work in the Critical Care Unit by stratified random sampling. The instrument was a set of questionnaires that was tested for content validity index by the experts, it was equal to 1.00. The Cronbach’s alpha coefficient of the transformational leadership of head nurses’ questions was equal to .98, and the one of the organizational commitment questionnaire was equal to .91. The research results were found that the transformational leadership of head nurses was moderately correlated with the organizational commitment of registered nurses at a statistically significant level of .01 (r=.588, p=.000). Hence, promoting the transformational leadership to head nurses to provide the registered nurses in Critical Care Unit at Police General Hospital is increased the organizational commitment.